2000
DOI: 10.1007/s001980050005
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Absorption in Postmenopausal Osteoporosis: Benefit of HRT Plus Calcitriol, but not HRT Alone, in both Malabsorbers and Normal Absorbers

Abstract: In a randomized trial involving 71 postmenopausal osteoporotic women with vertebral compression fractures, radiocalcium absorption studies using the (45)Ca single isotope method (alpha) were performed at baseline and after 8 months of treatment with either continuous combined hormone replacement therapy (HRT, as piperazine estrone sulfate 0.625-0.937 mg daily +/- medroxyprogesterone acetate 2.5 mg daily depending on uterine status) or HRT plus calcitriol 0. 25 microg twice daily. A calcium supplement of 600 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
1
7
0
1
Order By: Relevance
“…5) Holzherr et al 6) and Kalu 7) reported similar observations in human and animals, and our previous report also agreed with these results that ovarian hormone deficiency impaired ability of calcium absorption in rats everted intestinal sacs. 8) The presence of estrogen receptors in rat duodenal cells were confirmed and estrogen stimulates intestinal calcium absorption via an estrogen receptor.…”
Section: Ingestion Of Raffinose Promotes Calcium Absorption In the Lasupporting
confidence: 87%
“…5) Holzherr et al 6) and Kalu 7) reported similar observations in human and animals, and our previous report also agreed with these results that ovarian hormone deficiency impaired ability of calcium absorption in rats everted intestinal sacs. 8) The presence of estrogen receptors in rat duodenal cells were confirmed and estrogen stimulates intestinal calcium absorption via an estrogen receptor.…”
Section: Ingestion Of Raffinose Promotes Calcium Absorption In the Lasupporting
confidence: 87%
“…In elderly people, diminished renal function due to aging leads to a decrease in renal conversion to 1,25(OH) 2 D 3 [12] . Calcitriol [1,25(OH) 2 D 3 ] plays an important role in promoting bone formation, and D-hormone analogs prevent falls to a greater extent than does ordinary vitamin D. Therefore, the use of D-hormone analogs has been advocated for the treatment of osteoporosis in many studies [13][14][15] . Because patients who are treated with 0.5 μg/d or 1.0 μg/d of calcitriol tend to develop hypercalcinuria, serum and urinary calcium levels should be examined regularly, and the calcitriol regime should be examined intermittently.…”
Section: Introductionmentioning
confidence: 99%
“…In several other countries, studies demonstrated the clinical effectiveness of long-term calcitriol supplement in postmenopausal osteoporosis [3][4][5][6]. While an impaired intestinal calcium absorption is partly responsible for postmenopausal osteoporosis [3,4], Riggs and Nelson successfully demonstrated that calcium absorption could be normalized by small doses of calcitriol in postmenopausal osteoporosis [5].…”
mentioning
confidence: 99%